2007
DOI: 10.1021/ma062781f
|View full text |Cite
|
Sign up to set email alerts
|

SANS Characterization of an Anisotropic Poly(vinyl alcohol) Hydrogel with Vascular Applications

Abstract: Poly(vinyl alcohol) (PVA) hydrogels are formed by physical cross-linking through freeze/thaw cycles. By controlling the stress applied during the freeze/thaw process, anisotropic PVA hydrogels can be produced. An anisotropic PVA hydrogel conduit that mimics the nonlinear and anisotropic mechanical properties displayed by porcine aorta was developed. Preliminary structural characterization of isotropic and anisotropic PVA samples using small-angle neutron scattering reveals a polymer mesh cross-linked by crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 35 publications
3
99
1
Order By: Relevance
“…Such factors may influence the motion of the biomodeling when there is pulsatile flow in its lumen, as may the mechanical interaction between the biomodeling and the interventional devices during the training of endovascular intervention. Methods of representing these factors of a blood vessel with PVA-H have been reported by Wan et al (23) and Millon et al (24), (25) . Wan et al first indicated that PVA-H can represent the nonlinearity of a blood vessel in a tensile test by performing freeze-thaw cycles, which is a method in which PVA gel is repeatedly frozen and thawed.…”
Section: Discussionmentioning
confidence: 99%
“…Such factors may influence the motion of the biomodeling when there is pulsatile flow in its lumen, as may the mechanical interaction between the biomodeling and the interventional devices during the training of endovascular intervention. Methods of representing these factors of a blood vessel with PVA-H have been reported by Wan et al (23) and Millon et al (24), (25) . Wan et al first indicated that PVA-H can represent the nonlinearity of a blood vessel in a tensile test by performing freeze-thaw cycles, which is a method in which PVA gel is repeatedly frozen and thawed.…”
Section: Discussionmentioning
confidence: 99%
“…[87][88][89] Recent work resulted in a strain-induced aligned hydrogel that has extremely high Adv. Mater.…”
Section: Mechanical Strainmentioning
confidence: 99%
“…[88] During the prestretching process, polymer chains of chemically crosslinked poly(acrylic acid-co-acrylamide) hydrogels could be aligned along the stretched direction at the molecular scale. Then, Fe 3+ -mediated physical crosslinking fixed this structure and improved the mechanical strength of the aligned network.…”
Section: Mechanical Strainmentioning
confidence: 99%
“…That being said, the use of hydrogels as cryoprotectants for cells in conjunction with cryogelation processes has been demonstrated to successfully create cell-loaded macroporous gel scaffolds, albeit with some loss of cell activity following the freezing process. [70] Furthermore, although the rates of heating and cooling and the number of freeze/thaw cycles conducted can at least in part be used to rationally control the pore size and distribution generated, [71,72] the generated pores still typically have a broad pore size distribution and minimal if any directionality. Tam et al have demonstrated the possible benefits of adding typical cryoprotectant carbohydrates such as d-galactose, d-glucose, d-trehalose, or d-sucrose to the pre-gel solution, as all these sugars interact with water to alter the nature of ice crystallization and thus create more transparent hydrogels with improved pore size control.…”
Section: Cryogelationmentioning
confidence: 99%